Recent advances in electronic skins: material progress and applications - Cao, Hua-Li; Cai, Sui-Qing (Frontiers in Bioengineering and Biotechnology, 2022)
Electronic skins are currently in huge demand for health monitoring platforms and personalized medicine applications. To ensure safe monitoring for long-term periods, high-performance electronic skins that are softly interfaced with biological tissues are required. Stretchability, self-healing behavior, and biocompatibility of the materials will ensure the future application of electronic skins in biomedical engineering. This mini-review highlights recent advances in mechanically active materials and structural designs for electronic skins, which have been used successfully in these contexts. Firstly, the structural and biomechanical characteristics of biological skins are described and compared with those of artificial electronic skins. Thereafter, a wide variety of processing techniques for stretchable materials are reviewed, including geometric engineering and acquiring intrinsic stretchability. Then, different types of self-healing materials and their applications in electronic skins are critically assessed and compared. Finally, the mini-review is concluded with a discussion on remaining challenges and future opportunities for materials and biomedical research.